A Geospatial Analysis of Distances to Hospitals that Admit Pediatric Asthma Patients. (2nd November 2019) - Fishe, Jennifer; Finlay, Erik; Palmer, Sam; Hendry, Phyllis
Abstract: Objective : Pediatric care is now concentrated in urban specialty centers ("regionalization"), even for common conditions such as asthma. At the same time, rural emergency medical services (EMS) faces challenges related to adequate workforce staffing and financing. This statewide study describes how regionalization of pediatric inpatient care for asthma exacerbations affects EMS operations, particularly for rural agencies. Methods: This is a statewide cross-sectional study of EMS encounters for pediatric asthma in patients aged 2–18 years from 2011 to 2016 using Florida's EMS Tracking and Reporting System (EMSTARS) database. EMSTARS encounters were deterministically linked to Florida's Agency for Healthcare Administration (AHCA) database. We categorized AHCA hospital facilities that received included patients by whether they did or did not admit pediatric asthma patients during the study period ("admitting facility"). We used geospatial analysis to map the EMS agency's home county and the admitting facilities addresses. For each county in Florida, we calculated the average estimated EMS travel distance to the nearest admitting facility using a dasymetric mapping approach. Results: The study included a total of 11, 226 EMS pediatric asthma encounters, of which 11, 153 (99%) matched to an EMS home county. AHCA data was available for 3, 812 (34%) patients. Most counties with distances to admitting facilities less than or equal to 15 miles were urban (31 of 39). For distances of 31–45 miles to an admitting facility, 7 of 8 of counties were rural, and for distances greater than 46 miles, all 4 counties were rural. Conclusions: In this statewide study in Florida, we found long average estimated EMS travel distances to admitting facilities for Florida's pediatric population in rural counties for pediatric asthma exacerbations. Those long distances have great implications for rural EMS operations, including pediatric destination decisions, transport times, and availability for others who call 9-1-1. Further research on bypass and secondary transport rates, and outcomes for asthma and other pediatric conditions are required to further characterize pediatric regionalization's impact on rural EMS.